2003
DOI: 10.1097/01.coc.0000027416.15170.53
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serum IL-18 and Nitric Oxide Activity in Breast Cancer Patients at Operable Stage

Abstract: Interleukin-18 (IL-18) is a multifunctional cytokine that was previously termed interferon-gamma-inducing factor. It has been suggested that serum IL-18 level may be used as a prognostic factor in some cancer types. Nitric oxide is a potent biologic molecule involved in the pathogenesis of cancer. In this study, we measured serum IL-18 and nitrate + nitrite levels in 56 patients with nonmetastatic breast cancer and 14 control subjects. Serum IL-18* and nitrate + nitrite** levels were significantly higher in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
1
17
1
1
Order By: Relevance
“…As mentioned above, it seems that NO is mostly produced in cancer cells by iNOS. Most investigators found an adverse prognostic significance for iNOS expression (28)(29)(30) and nitrotyrosine tumor staining (which reflects intracellular NO levels) (21), whereas there is no direct evidence from the literature for the prognostic significance of plasma/serum NO levels (31,32). In the present study, high plasma NO levels predicted poor survival only in univariate analysis, apparently because of their direct correlation with the number of involved organs.…”
Section: Patients ---------------------------------------------------contrasting
confidence: 47%
“…As mentioned above, it seems that NO is mostly produced in cancer cells by iNOS. Most investigators found an adverse prognostic significance for iNOS expression (28)(29)(30) and nitrotyrosine tumor staining (which reflects intracellular NO levels) (21), whereas there is no direct evidence from the literature for the prognostic significance of plasma/serum NO levels (31,32). In the present study, high plasma NO levels predicted poor survival only in univariate analysis, apparently because of their direct correlation with the number of involved organs.…”
Section: Patients ---------------------------------------------------contrasting
confidence: 47%
“…21 Nonetheless, IL-18 is increased in the circulation of patients with different types of cancer. [22][23][24][25][26] Intriguingly, in an experimental tumor model, IL-18 mediated tumor progression through the enhancement of cancer cells' adhesive properties to the vascular endothelium or through proangiogenic activity. 27 Thus, the role of IL-18 in tumor biology and therapy remains a controversial issue.…”
mentioning
confidence: 99%
“…3 Here we report elevated serum levels of bioactive IL-18 in patients afflicted with pancreatic carcinoma. In fact, elevated serum levels of IL-18 have been observed in other tumors including colon carcinoma, 55 lung cancer, 55 hematological malignancies, including myeloma, 56,57 breast cancer, 58,59 gastric carcinoma, 60 esophageal carcinoma, 61 bladder cancer, 62 renal cell carcinoma 63 and head and neck carcinoma. 64 Generally, IL-18 production has been linked to aggressive tumor development and shorter survival times.…”
Section: Discussionmentioning
confidence: 99%